2014
DOI: 10.3390/jmse2020437
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Storm Surge Threat of Hurricane Sandy with the National Weather Service SLOSH Model

Abstract: Numerical simulations of the storm tide that flooded the US Atlantic coastline during Hurricane Sandy (2012) are carried out using the National Weather Service (NWS) Sea Lakes and Overland Surges from Hurricanes (SLOSH) storm surge prediction model to quantify its ability to replicate the height, timing, evolution and extent of the water that was driven ashore by this large, destructive storm. Recent upgrades to the numerical model, including the incorporation of astronomical tides, are described and simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 9 publications
3
43
0
Order By: Relevance
“…Both of these comparisons used different wind field models than used operationally in SLOSH. Forbes et al, 7 using standard operational wind fields, obtained relatively unbiased results with a standard deviation of about 25% in peak surge. For this magnitude of error, SLOSH increases surge uncertainty, over that inherent in the storm track forecast, by 3-12% in 24 h forecasts and 2 to 17% in 48-h forecasts.…”
Section: Estimating Tropical Cyclone Surge Hazard On the Scale Of Daysmentioning
confidence: 99%
“…Both of these comparisons used different wind field models than used operationally in SLOSH. Forbes et al, 7 using standard operational wind fields, obtained relatively unbiased results with a standard deviation of about 25% in peak surge. For this magnitude of error, SLOSH increases surge uncertainty, over that inherent in the storm track forecast, by 3-12% in 24 h forecasts and 2 to 17% in 48-h forecasts.…”
Section: Estimating Tropical Cyclone Surge Hazard On the Scale Of Daysmentioning
confidence: 99%
“…Both of these comparisons used different wind field models than used operationally in SLOSH. Forbes et al [20], using standard operational wind fields, obtained relatively unbiased results with a standard deviation of about 25 % in peak surge. For this magnitude of error, SLOSH increases surge uncertainty, over that inherent in the storm track forecast, by 3-12 % in 24-h forecasts and 2-17 % in 48-h forecasts.…”
Section: Estimating Tropical Cyclone Surge Hazard On the Scale Of Daysmentioning
confidence: 99%
“…On one hand, it can be argued uncertainties in realtime and forecast storm characteristics justify the use of relatively crude resolution and neglect of some physical terms in Fig. 1 Concept of information needs for decision-making over a range of time scales (modified from [9]) forecast surge simulations, e.g., the application of the SLOSH model [20] in the US. On the other hand, accurate prediction of storm surges in coastal areas, particularly inland inundation, requires high resolution and inclusion of all contributing physical processes in the simulations, such as waves along coasts typical of many Caribbean and Pacific regions [68] and the coupled influence of river flow and surges during landfall [41,42].…”
Section: Estimating Tropical Cyclone Surge Hazard On the Scale Of Daysmentioning
confidence: 99%
“…Forbes et al (2014) [13] showed a large ensemble spread of surge predictions using SLOSH for Sandy around NYC, but did not discuss the origin of that water level spread. Wind and pressure forcing for SLOSH are geometrically circular, thus unrepresentative of the large asymmetries observed during Sandy.…”
Section: Motivationmentioning
confidence: 99%
“…Forbes et al [13] showed that the NWS Sea, Lake, and Overland Surges from Hurricanes (SLOSH) model [14] could realistically simulate the Sandy water levels using an ensemble of tracks and intensities from the National Hurricane Center. Both Forbes et al [13] and Georgas et al [12] illustrated that Sandy's observed flooding was not a worst-case scenario for this event given the variations in Sandy's track and phase of the tide landfall that might have occurred.…”
Section: Introductionmentioning
confidence: 99%